Associations of Complementary Feeding Practice History and Protein Adequacy Level with Childhood Stunting in the Working Area of Puskesmas Bantaran in Probolinggo Regency: HUBUNGAN ANTARA RIWAYAT PEMBERIAN MP-ASI DAN KECUKUPAN PROTEIN DENGAN KEJADIAN STUNTING PADA BALITA DI WILAYAH KERJA PUSKESMAS BANTARAN KABUPATEN PROBOLINGGO - Riza Amalia; Ade Lia Ramadani; Lailatul Muniroh (Media Gizi Indonesia, 2022)
Stunting is often associated with too early complementary feeding time and inadequate protein intake. The purpose of this study was to analyze the relationship between the practice of complementary feeding and the level of protein adequacy with the incidence of stunting in toddlers in the working area of Puskesmas Bantaran Probolinggo regency, East Java. Research used observational analytic with retrospective case control design. The sample were 22 stunted group and 22 non-stunted control group who met the inclusion criteria, and taken by simple random sampling. The sample was a stunting locus village toddler in the working area of Puskesmas Bantaran, Probolinggo Regency with mother as respondents. Data collection instruments included questionnaires of characteristic, SQ-FFQ to assess protein adequacy, and microtoise to measure height. Analysis using Chi-Square and Spearman test. The results showed that stunted toddlers get inappropriate complementary feeding (81.8%) and deficit of protein intake (81.8%). Non-stunted toddlers get the right complementary feeding practices (63.6%) and adequate protein intake (59.1%). There is a relationship between the practice of complementary feeding (p=0.002, OR=7.87) and the level of protein adequacy (p=0.005, OR=6.5) with the incidence of stunting in toddlers. The conclusion of this study is that toddlers with improper complementary feeding practices are 7.87 times higher risk of stunting and toddlers with adequate levels of protein deficit are 6.5 times higher risk of stunting. Mothers should be able to increase the amount of protein intake and proper complementary feeding.